2013
DOI: 10.4037/ajcc2013158
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the New International Sepsis Guidelines for Nursing Care

Abstract: Sepsis is a serious worldwide health care condition that is associated with high mortality rates, despite improvements in the ability to manage infection. New guidelines for the management of sepsis were recently released that advocate for implementation of care based on evidence-based practice for both adult and pediatric patients. Critical care nurses are directly involved in the assessment of patients at risk for developing sepsis and in the treatment of patients with sepsis and can, therefore, affect outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
9

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 62 publications
0
32
0
9
Order By: Relevance
“…Nursing implications of the revised Surviving Sepsis guidelines are summarized in this issue of AJCC by Drs Ruth Kleinpell, Leanne Aitken, and Christa Schorr, who were members of the revision committee. 4 Revisions to these 2 important guidelines illustrate how recent publications inform changes in clinical guidelines. Recommendations for practice continue to change as new research confirms, refutes, or modifies previous practices.…”
Section: Guidelines For Clinical Practicementioning
confidence: 99%
“…Nursing implications of the revised Surviving Sepsis guidelines are summarized in this issue of AJCC by Drs Ruth Kleinpell, Leanne Aitken, and Christa Schorr, who were members of the revision committee. 4 Revisions to these 2 important guidelines illustrate how recent publications inform changes in clinical guidelines. Recommendations for practice continue to change as new research confirms, refutes, or modifies previous practices.…”
Section: Guidelines For Clinical Practicementioning
confidence: 99%
“…Sometimes, the family of the patient must make a big effort to understand the criticality of the clinical picture and the nurse plays a fundamental role which is recognized by the international literature, to help family members to understand the situation, through continuous reports and talks. 1,22,23 Generally, for treatment of hospitalized patients with sepsis, it is fundamental: 6 i) to disseminate information on the new guidelines to the team members; ii) to include discussion of the guidelines during unit clinical care meetings and clinical rounds; iii) to constitute a multidisciplinary team and outline a timeline for implementing the guidelines; iv) to use the new guidelines as a performance improvement initiative for the Intensive Care Unit as well as noncritical care areas to improve recognition and treatment of patients with sepsis. Specific areas include: i) aid in the early identification of sepsis including recognizing patients at risk for developing sepsis (patients who are elderly, immunocompromised, patients with surgical/invasive procedures, indwelling catheters, mechanically ventilated patients) and monitoring physical assessment parameters including vital signs and perfusion status (urine output, mental status changes, skin color); ii) to provide comprehensive sepsis treatment (circulatory support with fluids, inotropes, and vasopressors; supportive treatment with oxygenation and ventilation; antibiotic administration; sepsis guideline recommendation measures; monitor and report patient response to treatment); iii) to promote patient and family centered care (patient and family teaching, addressing the needs of families of critically ill patients, setting goals of care, and holding family care conferences to discuss goals of care).…”
Section: 2mentioning
confidence: 99%
“…1,5 This can be considered a continuum that can evolve from one infection status to multi-organ failure that could lead to death. The origin of sepsis is varied, it was found that sepsis of respiratory origin is the most common in the industrialized world 4,5,[13][14][15] with an incidence rate ranging between 35% and 50%, followed by infections of urinary tract, intra-abdominal, catheter-related blood stream infection, device-related, central nervous system and others (e.g., cellulitis, intra-articular).…”
Section: Definition Of Sepsismentioning
confidence: 99%
“…[37][38][39] In tracking metrics such as time to measurement of lactate levels, time to collection of samples for blood cultures, time to administration of antibiotics, and other quality goals, individual institutions can improve sepsis care and outcomes. Using the new clinical criteria in Sepsis-3, for example, tracking use of SOFA or qSOFA, to evaluate possible additional sepsis-related metrics further may also be helpful.…”
Section: Implications For Clinical Practicementioning
confidence: 99%